Technology for successful training in vocational education //Tecnología para una formación exitosa en educación vocacional - Vaganova, Olga I.; Kutepov, Maxim M.; Chelnokova, Elena A.; Harabadjah, Meliya N.; Merzlyakova, Natalya S. (Revista de la Universidad del Zulia, 2020)
Abstract One of the leading directions in the development of vocational education in the context of modern educational paradigm is humanization, focused on students’ personality, taking into account its needs and characteristics in the development of professional competence. Humanization is closely related to the implementation of a personal approach that promotes individualization of educational process, which in turn allows each student to be included in active cognitive activity. The search for means and methods of training students who meet modern requirements has led to the demand for implementation of successful learning technology in vocational education. The technology of successful learning in vocational education contributes to the creation of conditions in which the student’s self-expression becomes more comfortable due to experiencing a state of joy and satisfaction from the results achieved. The purpose of the article is to review the experience of implementing technology of successful learning at a pedagogical university. The article reveals the essence of the concept of "technology of successful learning", its features and impact on the training process of students of vocational schools. The study allowed us to establish the impact of implementation of successful learning technology on student motivation. In the process of research, the level of motivation of students to study professional and pedagogical courses was established. The main motives of students are revealed. The study presented several dozen motives, among which, after conducting a statistical analysis, professional, educational, cognitive and prestige motives were highlighted. Comparison of the results at the beginning and end of the study revealed an improvement in indicators, an increase in students’ motivation to study courses. The wide possibilities for the implementation of successful learning technology make it possible to form a need for a deeper study of the content, for self-organization and professional self-improvement of students. Resumen Una de las direcciones principales en el desarrollo de la formación profesional en el contexto del paradigma educativo moderno es la humanización, centrada en la personalidad de los estudiantes, teniendo en cuenta sus necesidades y características en el desarrollo de la competencia profesional. La humanización está íntimamente relacionada con la implementación de un enfoque personal que promueve la individualización del proceso educativo, lo que a su vez permite que cada alumno sea incluido en la actividad cognitiva activa. La búsqueda de medios y métodos para capacitar a los estudiantes que cumplan con los requisitos modernos ha llevado a la demanda de implementación de tecnología de aprendizaje exitosa en la educación vocacional. La tecnología del aprendizaje exitoso en la educación vocacional contribuye a la creación de condiciones en las que la autoexpresión del alumno se vuelve más cómoda al experimentar un estado de alegría y satisfacción por los resultados obtenidos. El propósito del artículo es revisar la experiencia de implementar tecnología de aprendizaje exitoso en una universidad pedagógica. El artículo revela la esencia del concepto de "tecnología de aprendizaje exitoso", sus características e impacto en el proceso de formación de los estudiantes de las escuelas profesionales. El estudio nos permitió establecer el impacto de la implementación de tecnología de aprendizaje exitosa en la motivación de los estudiantes. En el proceso de investigación se estableció el nivel de motivación de los estudiantes para cursar cursos profesionales y pedagógicos. Se revelan los principales motivos de los estudiantes. El estudio presentó varias decenas de motivos, entre los que, tras realizar un análisis estadístico, se destacaron motivos profesionales, educativos, cognitivos y de prestigio. La comparación de los resultados al inicio y al final del estudio reveló una mejora en los indicadores, un aumento en la motivación de los estudiantes para estudiar cursos. Las amplias posibilidades para la implementación de tecnología de aprendizaje exitosa hacen posible que se forme una necesidad de un estudio más profundo del contenido, para la autoorganización y la superación profesional de los estudiantes.